Cold snare polypectomy: Indications, devices, techniques, outcomes and future. Issue 4 (8th January 2019) - Horiuchi, Akira; Ikuse, Tamaki; Tanaka, Naoki
Abstract : Colonoscopy has been shown to reduce the risk of colon cancer by enabling the removal of precancerous lesions. Although cold snare and hot snare polypectomy have similar retrieval rates and complete resection rates, rates of delayed bleeding tend to be lower with cold snare polypectomy than with hot snare polypectomy, especially for patients taking antithrombotic agents. However, among cold snares there may be differences in terms of the completeness of polyp excision, as complete removal appears more likely with thin‐wire dedicated cold snares compared to the traditional, thick‐wire cold snares. Cold snare polypectomy may be especially well suited for use in patients taking antithrombotic agents, due to its minimal risk of delayed bleeding. Histological analyses suggest that cold snare polypectomy causes less damage to blood vessels in the submucosal layers, which results in a reduced incidence of hemorrhage compared to hot snare polypectomy. However, cold snare removal of small polyps may result in fragmentation of small specimens during collection and concerns as to whether the resection is complete. An endoscopy biomarker of effective cold snare polypectomy technique is needed to ensure complete removal of non‐pedunculated colorectal polyps ≤10 mm. Future uses of cold snare polypectomy may include piecemeal removal of sessile serrated adenoma/polyp lesions >10 mm. Currently, cold snare polypectomy should be considered a primary method for colorectal polyps of less than 10 mm, especially those in the 4‐ to 10‐mm range.